Determinants of commercialization among onion producer households in southern Ethiopia: a double hurdle approach - Wondim, Melkamu Tilaye; Geyo, Guta Bukero (Frontiers in Environmental Economics, 2024)
This study examined the determinants of onion commercialization of smallholder farmers in the Wolayita and Gomo zones of southern Ethiopia. Both primary and secondary data were used in this study. Primary data were collected from randomly selected 160 onion producers by using a structured questionnaire. Both descriptive statistics and the double-hurdle econometric model were employed in the analysis. The descriptive statistics showed that the mean commercialization level of smallholder farmers in the study area was 79.51 % which revealed that the producers of onion in the study area mainly marketing their produce. Using the econometric model the first-stage double hurdle results revealed that family size, farming experience, frequency of extension contact, and distance to the nearest market were factors significantly affecting the market participation decision of onion producers. The second stage of the double hurdle results indicates that education level, family size, frequency of extension contact, land size allotted for onion production, and distance to the nearest market were factors that significantly affected the level of onion commercialization. Therefore, policies aimed at increasing farmers' access to better road networks and transportation facilities, improving access to education, promoting agricultural training programs, and improving extension services are recommended to improve the commercialization of onion production.